Feasibility analysis of CT-guided thermal ablation of multiple pulmonary nodules combined with intraoperative biopsy - Shan, Yu-Qing; Wang, Hai-Yu; He, Xiao-Ning; Jiang, Shuang-Sheng; Wang, Hui-Hui; Lin, Fan-Xia (Frontiers in Radiology, 2022)
Purpose To analyze the safety and feasibility of computed tomography (CT)-guided thermal ablation of multiple pulmonary nodules combined with intraoperative biopsy. Methods The data of 431 patients with 540 lung nodules undergoing CT-guided biopsy or ablation were retrospectively analyzed. Biopsy-only group (A): 107 patients (107 lesions) received CT-guided percutaneous lung biopsy only; Ablation-only group (B): 117 cases (117 lesions) only received CT-guided thermal ablation; Single focal ablation combined with biopsy group (C): 103 patients (103 lesions) received CT-guided thermal ablation combined with intraoperative immediate biopsy; Multifocal ablation combined with biopsy group (D): 104 patients (213 lesions) received CT-guided thermal ablation combined with intraoperative biopsy. The success rate of this technique was calculated, the complications were recorded, and the positive rate of pathological diagnosis of the specimens was evaluated (the tissue specimens could be confirmed as positive by pathological diagnosis). Results All 431 patients with pulmonary nodules successfully completed the operation, and the technical success rate was 100% (431/431). In group A, hemoptysis occurred in seven cases after operation, while no hemoptysis was observed in the other groups. Pneumothorax occurred in 8 cases in group A, 14 cases in group B, 11 cases in group C, and 13 cases in group D. Hydrothorax occurred in 4 cases in group A, 7 cases in group B, 5 cases in group C and 9 cases in group D, and there were no significant differences between the groups. The positive rate of pathological diagnosis was 84.1% (90/107) in group A, 81.5% (84/103) in group C, and 82.6% (176/213) in group D, and there was no significant difference among the groups (P > 0.05). A total of 15 cases in group C and 23 cases in group D underwent gene testing and analysis, and the biopsy tissue samples all met quality control standards. Conclusion CT-guided thermal ablation of multiple pulmonary nodules combined with intraoperative biopsy does not prolong the length of hospital stay or increase the risk of postoperative complications. It can meet the requirements of clinical, pathological and genetic testing, and is safe and reliable.